Spectrophotometric Determination of Mercury Ion After Liquid-Liquid Extraction with Toluidine Blue-O - Parham, H.; Noorizadeh, H.; Nekouei, F. (Asian Journal of Chemistry, 2011)
A simple and highly sensitive extraction-spectrophotometric determination of mercury is described. The ion-associate formed between the HgI42- and toluidine blue-O is extracted with dichloromethane at pH 6. The absorption maximum of the extracted species occurs at 593 nm, the molar absorptivity being 1.42 × 105 L mol-1 cm-1. The calibration curve was linear in the concentration range of 0.1-2.5 μg mL-1 of Hg2+ with a correlation coefficient of 0.9995. The limit of detection (LOD) is 0.021 μg mL-1. The relative standard deviation (RSD) at 0.6 and 1.2 μg mL-1 of mercury were 2.12 and 3.08 % (n = 8), respectively. The method was applied for measuring the amount of mercury in water samples.